2012
DOI: 10.2355/isijinternational.52.369
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Additives on Cokemaking from a Semi-soft Coking Coal during Microwave Heating

Abstract: Coke was produced from a Waterberg semi-soft coking coal using microwave heating and selected microwave susceptors. Waterberg semi-soft coking coal is poorly susceptible to microwave heating, especially below 500°C, and therefore requires microwave susceptors. Susceptors were selected from ferroalloy fines and their respective ores.Various batch experiments were performed on compressed discs utilizing a resonant microwave cavity at a constant 915 MHz frequency to heat a batch of about 5 to 7 kg of the semi-sof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Coetzer and Rossouw have used microwave treatment to produce high quality cokes from a Waterberg semi-soft coking coal in 2 -3 hours using microwave receptors to heat the coal indirectly [24]. However, according to the theory presented above, some or even all coals could be heated to coking temperatures without the addition of microwave receptors.…”
Section: Introductionmentioning
confidence: 99%
“…Coetzer and Rossouw have used microwave treatment to produce high quality cokes from a Waterberg semi-soft coking coal in 2 -3 hours using microwave receptors to heat the coal indirectly [24]. However, according to the theory presented above, some or even all coals could be heated to coking temperatures without the addition of microwave receptors.…”
Section: Introductionmentioning
confidence: 99%
“…Similar studies have not demonstrated such rapid coking potential. Coetzer and Rossouw 24 produced lump coke from a semi-soft coking coal with microwave susceptors over a period of 2-3 hours, while…”
Section: Microwave Test Resultsmentioning
confidence: 99%
“…8,20 Several studies have used susceptors to increase the microwave absorbance of coal. [21][22][23][24] However, Lester et al 8 and Binner et al 20 showed that it is possible to produce coke with a similar vitrinite reflectance to that of conventional cokes without the use of susceptors, although the cokes formed were only in powdered form. The physical structure of coke is a key feature of blast furnace operation, 25 as it provides the bed support and permeability for the liquid phase drainage and upward flow of blast furnace gases.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that large values of ε′ and ε″ will result in surface heating and low penetration depth. 33,34 At the initial liquefaction stage, most liquefaction solvent was not able to penetrate into wood particles and remained "free" in the system. Therefore, the liquefaction system had high ε′ and ε″ values close to that of the liquefaction solvent.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…It was observed that the range of temperatures for the higher penetration depths overlapped with the range of temperatures for the phase transition in the liquefaction system, specifically when the liquid/solid mixture transformed into a viscous liquid between 90 to 110 °C. It has been reported that large values of ε′ and ε″ will result in surface heating and low penetration depth. , At the initial liquefaction stage, most liquefaction solvent was not able to penetrate into wood particles and remained “free” in the system. Therefore, the liquefaction system had high ε′ and ε″ values close to that of the liquefaction solvent.…”
Section: Resultsmentioning
confidence: 99%